Marketingová komunikace konkrétního produktu - Pospíšil, Lukáš (Vysoké učení technické v Brně. Fakulta podnikatelská, 2023)
Diplomová práce je zaměřená na doplnění a úpravy marketingové komunikace konkrétního magisterského studijního programu. Teoretická část se zabývá problematikou vysoké školy se zaměřením na marketingový mix, marketingovou komunikaci a rozhodování uchazečů. Analytická část je zaměřena na současný stav, kdy na základě výstupů analýz jsou zpracovány návrhy. Realizace návrhů povede především ke zvýšení povědomí o studijním programu, což pomůže přinést i navýšení počtu přihlášek.

The diploma thesis focuses on the addition and modification of marketing communication of a specific master's degree programme. The theoretical part deals with the issues of the university, focusing on the marketing mix, marketing communication and applicants' decision-making. The analytical part focuses on the current state of affairs, where proposals are made based on the outcomes of the analyses. The implementation of the proposals will mainly lead to an increase in the awareness of the study programme, which will also help to bring about an increase in the number of applications.
Marketing Communication of a Specific Product
Keywords: marketing; marketing na vysokých školách; marketingová komunikace; studijní program; online marketing; marketing; marketing at universities; marketing communication; study program; online marketing